Economic Challenges Facing Japan's Regional Areas (Springer Singapore, 2018)
This book analyzes issues related to economic challenges for Japan's regional revitalization. Japan's responses to such challenges and to the problem of an aging population are of deep interest to the nations outside of Japan. This book brings together 19 articles contributed by Japan's leading scholars, originally prepared for an online policy information portal, SPACE NIRA launched by the Nippon Institute for Research Advancement (NIRA) with Dr. Tatsuo Hatta, President of the Asian Growth Research Institute, as its General Editor. This book is a significant and useful reference for all scholars, students, and individuals with an interest in current policy issues in Japan.